Diverse Combinatorial Biosynthesis Strategies for C-H Functionalization of Anthracyclinones - Wang, Rongbin (American Chemical Society, 2026)
Streptomyces spp. are "nature's antibiotic factories" that produce valuable bioactive metabolites, such as the cytotoxic anthracycline polyketides. While the anthracyclines have hundreds of natural and chemically synthesized analogues, much of the chemical diversity stems from enzymatic modifications to the saccharide chains and, to a lesser extent, from alterations to the core scaffold. Previous work has resulted in the generation of a BioBricks synthetic biology toolbox in Streptomyces coelicolor M1152ΔmatAB that could produce aklavinone, 9-epi-aklavinone, auramycinone, and nogalamycinone. In this work, we extended the platform to generate oxidatively modified analogues via two crucial strategies. (i) We swapped the ketoreductase and first-ring cyclase enzymes for the aromatase cyclase from the mithramycin biosynthetic pathway in our polyketide synthase (PKS) cassettes to generate 2-hydroxylated analogues. (ii) Next, we engineered several multioxygenase cassettes to catalyze 11-hydroxylation, 1-hydroxylation, 10-hydroxylation, 10-decarboxylation, and 4-hydroxyl regioisomerization. We also developed improved plasmid vectors and S. coelicolor M1152ΔmatAB expression hosts to produce anthracyclinones. This work sets the stage for the combinatorial biosynthesis of bespoke anthracyclines using recombinant Streptomyces spp. hosts.